TecDIY—Motivation methodology for the practical laboratories preparation and exams of electronics subject. Issue 1 (14th October 2019) - Rodriguez‐Sanchez, M. C.; Yahyaoui, Imene; Arredondo, B.; Martin, D.; Vaquero, J.
Abstract: This proposal is concerned with a new methodology named Tecnology and Electronics—Do It Yourself (TECDIY) with the aim to motivate students of the first course of systems and multimedia engineering grade to prepare the practical laboratories and the exams of Physics and Electronics subject. The methodology consists in integrating projects‐based learning (‐) and the motivation for the practical laboratories and exams using preprepared videos, models adaptation of the theory, exercises, and problems preparation Gymkana. In addition, TECDIY methodology is supported by an attendance registration system, which allows the students assistance to class to be verified and controlled. The study is performed by comparing indicators, namely the predelivery of the laboratories theoretic calculations, the problems delivery, and assistance to class, performed in three academic years (2013–2014, 2014–2015, and 2015–2016). The results of applying this method demonstrate a significant increase of these indicators, which means the efficiency of TECDIY method in motivating the students to prepare the exam and the practical laboratories.